Transforming Agriculture Students to lead Indian Farming sector - Didal, Vijay Kumar; K., Krishna G.; N., Nithin K.; Patil, Rajendragouda; Rao, R. Gowri Sankara (Indian Farming, 2021)
Agriculture is a dynamic fieldwhere several opportunities andchallenges come up practically on adaily basis. The agricultural educationis provided in a short span of fouryears. If the students need to betaught the updates, embracing theself-learning habit is the only way.The practical understanding andtechnological advancements must beunboxed to students by the faculty.The students will surely be motivatedenough to imbibe the knowledge,develop their understanding andpractically implement at the rightpoint of time.